Accountability, vedic & schumacher’s philosophy and autoethnography: An advocation for tax relief for sibling caregivers in Malaysia / Siva Subramanian A.R. Nair - Siva Subramanian, A.R. Nair (2015)

(untitled)
In line with its objective of being accountable to Malaysian society, the Government of Malaysia has shown full support for all efforts to enhance facilities for persons with disabilities and ensuring that these individuals are always well taken care of. This is evident from the enactment of the Persons with Disabilities Act 2008, and the signing of the instrument to ratify the United Nations Convention on the Rights of Persons with Disabilities. The government has recognised that caring for persons with disabilities is its responsibility but, judging from the sheer enormity of the number of such persons, this responsibility has been delegated to the individual families of the disabled over time, with the government providing assistance in numerous forms. The study raises the questions of why and how the (formal and moral) accountability operates within the context of religion, society and state and serves the underprivileged or marginalised people's interest such as disabled in the Malaysian society. The study endeavours to understand what motivates siblings to become caregivers and to this end attempts to develop a theoretical conceptualisation of accountability firstly by drawing from Vedic philosophy and secondly by providing an explanation from the philosophy of Schumacher. With this in place, the study advances to explore the state's role in supporting sibling caregivers. One form in which the State is able to support the families of persons with disabilities is through the provision of tax relief, which serves to reduce their income tax payable. This is meant to compensate them for the additional costs incurred in providing caregiving services. Although the relief never covers the full amount of costs incurred, it does provide some financial recompense. Additionally, the relief represents recognition of their contribution in taking care of a disabled person, thus providing caregivers a balm of satisfaction. Unfortunately, following the lineal ancestry principle, the tax relief is given only to parents taking care of children with disabilities, or to children taking care of their aged, sick or disabled parents but there is no tax relief is available in Malaysia to sibling caregivers. Interestingly, many other countries, including our immediate geographical neighbours of Thailand and Singapore, provide tax relief and credits to caregivers, irrespective of the relationship between them and the person to whom care is provided. As there is limited research in the area of what motivates siblings to become caregivers, especially in Malaysia, this study draws on the concept of accountability in existing literature (as viewed through the lens of Schumacher, a renowned philosopher), as well as from the principles expounded by the Vedas, to understand this motivation of sibling caregivers. In line with this motivation, this study intends to explore the state's role in supporting sibling caregivers. One suggestion is for the Government to provide a tax relief for sibling caregivers with both a token of compensation for the costs they have borne, as well as recognition of their personal, selfless contribution. This study is significant as it contributes to the literature in three aspects. First, it develops a conceptualisation of accountability viewed through the theoretical lens using Schumacher, ii and draws on Vedic philosophy to empirically examine the issue of motivation for sibling caregivers. Second, it uses the autoethnographic approach to suggest that the role of the State could be discharged through the introduction of a tax relief for sibling caregivers. Finally, it provides empirical evidence and support to guide policy direction with a view to harmonisation of fiscal policies within the geographical region.